Evgeniya Bilodid. Borys Grinchenko personality in the publications of the newspaper “Rada” - Bilodid, Evgeniya (Young Scholars Grinchenko – Seton International Journal, 2021)
Evgeniya Bilodid. Borys Grinchenko personality in the publications of the newspaper “Rada”. Abstract. The article analyzes the publishing activity of the daily Ukrainian newspaper Rada in order to study the figure and activities of Borys Grinchenko. It was established that the main issues that drew the attention of editors and readers were the work of the figure in the Kyiv society «Prosvita», familiarization of society with the works of the writer, and clarification of the topic concerning the tribute to his memory. The publicistic activity of Borys Grinchenko among the team of editors of The Rada newspaper was analyzed. It was established that special attention was paid to the issues of the use and status of Ukrainian language, the distribution of Ukrainian books and their value in the development of education. A review of materials on the subject of burial and tribute to the memory of Boris Grinchenko reveals the value of the literary and social activities of the deceased for future descendants. Were shown the attitude of people of different social categories to the activities of the writer and the somewhat exaggerated belauding of the figure by the authors and editors of The Rada newspaper. Based on the studied publications of the broadsheet, the role of the great figure during the times of the national revival and formation of the Ukrainian nation was investigated. Keywords: Borys Grinchenko, The Rada newspaper, Ukrainian language, nation, society «Prosvita», literature, tribute to the memory.